Molecular insights and inhibitory dynamics of flavonoids in targeting Pim-1 kinase for cancer therapy - Alhadrami, Hani A.; Sayed, Ahmed M.; Hassan, Hossam M.; Alhadrami, Albaraa H.; Rateb, Mostafa E. (Frontiers in Pharmacology, 2024)
Pim-1 kinase, a serine/threonine kinase, is often overexpressed in various cancers, contributing to disease progression and poor prognosis. In this study, we explored the potential of flavonoids as inhibitors of Pim-1 kinase using a combination of molecular docking and steered molecular dynamics (SMD) simulations. Our docking studies revealed two main binding orientations for the flavonoid molecules. The SMD simulations showed that the binding mode with higher pulling forces was linked to stronger inhibitory activity, with a strong positive correlation (R 2 ≈ 0.92) between pulling forces and IC50 values. Quercetin stood out as the most potent inhibitor, showing a pulling force of about 820 pN and an IC50 of less than 6 µM.Further dynamic simulations indicated that quercetin's hydroxyl groups at the C3, C-5 and C-7 positions formed stable hydrogen bonds with key residues GLU-121, Leu-44 and Val-126, respectively enhancing its binding stability and effectiveness. Our results emphasized the critical role of the hydroxyl group at the C-3 position, which plays a pivotal function in effectively anchoring these molecules in the active site of Pim-1 kinase. Principal component analysis (PCA) of Pim-1 kinase's conformational changes revealed that potent inhibitors like quercetin, galangin, and kaempferol significantly restricted the enzyme's flexibility, suggesting potential inhibitory effect. These findings provide insights into the structural interactions between flavonoids and Pim-1 kinase, offering a foundation for future experimental investigations. However, further studies, including in vitro and in vivo validation, are necessary to assess the pharmacological relevance and specificity of flavonoids in cancer therapy.